Slaughterhouse’s Animal Welfare Assessement at Bekasi City, West Java - Katyusa Nandini Dyah Pitaloka; Etih Sudarnika; Herwin Pisestyani (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
The quality of meat sold in Bekasi City is affected by the implementation of animal welfare during the slaughtering process in Slaughterhouses. The research aimed to analyze the animal welfare implementation during the slaughtering process at Bekasi City slaughterhouses. The data was conducted by observing the five-freedom implementation for five slaughterhouses throughout Bekasi City, from the shelter cages to the slaughter. Herding officers ensured no disturbance in the herding route, hitting only animals' backs when the animals stopped walking, and confirmed that animals did not pile up on the herding lane and that live animals did not see the slaughter process. However, some officers still wear clothing that contrasts with the environment, hit the animals repeatedly, and shout at the animals excessively during the herding process. Animal welfare aspects of the slaughter process, such as officers already in position when the animal enters the restraining box, the sharpness of the knife being checked before slaughtering, having a spare knife, and animals slaughtered less than 30 seconds after stunning, have been implemented by all officers. The butcher animal welfare implementation, such as checking the animals' death after being slaughtered, still needs to be improved. This research concluded that Bekasi City's slaughterhouse officers had implemented aspects of animal welfare. However, some improvements are still required through training to increase the competence of officers.